Effect of Post-Ruminal Urea Supply on Growth Performance of Grazing Nellore Young Bulls at Dry Season - Reis, Irene Alexandre [UNESP]; Souza, Mailza Gonçalves de [UNESP]; Granja-Salcedo, Yury Tatiana; Carvalho, Isabela Pena Carvalho de; Porcionato, Marco Aurélio De Felicio; Prados, Laura Franco; Siqueira, Gustavo Rezende [UNESP]; De Resende, Flávio Dutra [UNESP] (MDPI, 2023)
The objective of this study was to evaluate the effect of the use of post-ruminal urea on performance, nitrogen metabolism and the ruminal environment of Nellore cattle reared on pasture during the dry season. In experiment 1 (Exp. 1), nine ruminal-cannulated Nellore steers, 30 ± 2 months old (651 ± 45 kg body weight (BW)), were allotted to a 3 × 3 Latin triple square. In experiment 2 (Exp. 2), 84 Nellore bulls, 18 ± 3 months old (315 ± 84 kg BW), were distributed in complete randomized blocks, by initial BW. Protein supplements were supplied daily, in the amount of 2 g/kg BW, and consisted of either CONT: protein + conventional urea (50% CP), PRU: protein + post ruminal urea (50% CP) and U + PRU: protein + urea conventional + post-ruminal urea (70% CP). The paddocks were composed of Urochloa brizantha cv. Marandu grass. In Exp. 1, there was no treatment effect for DM, OM, NDF, forage intake, and CP, but there was a higher intake for PRU (p < 0.005) and a higher digestibility for U+ PRU (p = 0.001). There was no effect on ruminal pH or NH3-N concentration (p ≥ 0.232), but there was an interaction between treatment and time for them (p < 0.039). Furthermore, there was a treatment effect on the total SCFA concentration, with CONT being higher than the others. A difference in the acetate:propionate ratio was found (p < 0.027), with a greater relationship for PRU and U + PRU. A treatment effect (p = 0.049) was found for the propionate proportion, with a higher proportion in the CONT. Nitrogen intake was consequently lower for the CONT and higher urinary excretion for the U + PRU (p = 0.002). Animals supplemented with CONT showed a tendency to have more Bacteria and fewer Archaea (p = 0.086). In Exp. 2, there was a treatment effect for the disappearance rate of the supplement (p < 0.001). Intake was faster for PRU and CONT, but performance was not affected by PRU (p = 0.311). The use of post-ruminal urea alters the microbial population, but does not affect performance. Therefore, supplementation with post-ruminal urea presented similar results compared to conventional urea. Ruminal and blood parameters and animal performance were not influenced by treatments.
Keywords: efficient nitrogen utilization; non-protein nitrogen; performance; post-rumen supplementation